US–China Relations and the Second Trump Administration - Jingdong YUAN (East Asian Policy)
China and the United States are engaged in intensive competition in diplomatic, economic, technology and military domains where they vie for primacy in the Indo-Pacific region. With the demise of the engagement policy since President Richard Nixon’s historic visit to China in 1972, the nature of US–China relations has undergone fundamental changes. This will be a stress test to Beijing’s and Washington’s willingness and ability to manage, mitigate and de-escalate potential conflicts, especially over the Taiwan issue.